The value creation wheel: a meta-framework to create value for deimos group - Lima, Ana Teresa (2022)
In this work, the spotlight was on Deimos Group, an Aerospace Engineering company. Starting with the concept of value, this work leads to an explanation of the Value Creation Wheel (VCW) framework and a description of the paradoxes it may solve. Five case studies demonstrate how the framework was applied, namely in: 1) Identifying and engaging new clients for the PDGS & Data Systems division, 2) Finding new users for BETTER, 3) Developing an innovation ecosystem to apply the VCW in upcoming challenges, 4) Attracting the talent of Software Engineers, and 5) Developing a positioning strategy for Marine-EO.